2008
DOI: 10.1371/journal.pmed.0050178
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the California Tobacco Control Program on Personal Health Care Expenditures

Abstract: BackgroundLarge state tobacco control programs have been shown to reduce smoking and would be expected to affect health care costs. We investigate the effect of California's large-scale tobacco control program on aggregate personal health care expenditures in the state.Methods and FindingsCointegrating regressions were used to predict (1) the difference in per capita cigarette consumption between California and 38 control states as a function of the difference in cumulative expenditures of the California and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(93 citation statements)
references
References 19 publications
7
81
2
3
Order By: Relevance
“…18 In addition, the California program's estimated impact on reducing personal health-care expenditures has been approximately $86 billion to date. 47 In 2007, the Centers for Disease Control and Prevention (CDC) updated its recommendations on Best Practices for Comprehensive Tobacco Control Programs. 38 This document provides guidelines to all states to aid them in strengthening their implementation of comprehensive tobacco-control programs by including these components: state and community interventions, health-communication interventions, cessation inter- ventions, and surveillance and evaluation.…”
Section: Other Tobacco Productsmentioning
confidence: 99%
“…18 In addition, the California program's estimated impact on reducing personal health-care expenditures has been approximately $86 billion to date. 47 In 2007, the Centers for Disease Control and Prevention (CDC) updated its recommendations on Best Practices for Comprehensive Tobacco Control Programs. 38 This document provides guidelines to all states to aid them in strengthening their implementation of comprehensive tobacco-control programs by including these components: state and community interventions, health-communication interventions, cessation inter- ventions, and surveillance and evaluation.…”
Section: Other Tobacco Productsmentioning
confidence: 99%
“…Another study reported that from 1989 to 1999, the CTCP was associated with a 6% reduction in lung cancer incidence 17. Only one study evaluated the economic effect of the CTCP, estimating that the programme saved $86 billion in 2004 dollars of healthcare expenditures between 1989 and 2004 18. However, the long-term economic effect of the CTCP, including reduced smoking-related diseases (SRDs) and reduced smoking-related deaths, has not been documented.…”
Section: Introductionmentioning
confidence: 99%
“…For example, increasing taxes on cigarettes is reported to decrease the macrobehavior of smoking (Chaloupka, Stralf, & Leon, 2010;Hu & Mao, 2002). Further, decreases in macrobehavior of smoking have been associated with reduced per capita health care expenditures (Lightwood, Dinno, & Glantz, 2008). In this case, contingent response cost for behavior of many individuals results in positive cumulative effects at the societal level (and presumably prevention of health problems for many people at the individual level.…”
Section: Macrocontingencymentioning
confidence: 99%